2017
DOI: 10.1186/s12978-017-0373-7
|View full text |Cite
|
Sign up to set email alerts
|

Women’s determinant factors for preferred place of delivery in Dodoma region Tanzania: a cross sectional study

Abstract: BackgroundSkilled birth attendance is one of the key factors in improving maternal health but less than 50% of women in sub-Saharan African countries do not have the opportunity to be attended to by skilled personnel during childbirth. The aim of the study was to assess the factors determining women’s preference for a place to give birth in Dodoma Region, Tanzania.MethodsThis study employed a cross-sectional survey design using quantitative data collection and analysis methods. Data were collected using struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 23 publications
8
37
2
Order By: Relevance
“…In this study, the result revealed that disrespect and abuse during child birth, lack of antenatal care follow up, lack of support to get health service, and unsatisfactory delivery services in the health facilities were found to be reason for preference of home delivery among postnatal mothers. These study finding is in line with other studies results in Ethiopia, Nigeria, Nepal, Kenya and Tanzania respectively [15,18,20,22,[27][28][29][30]32].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the result revealed that disrespect and abuse during child birth, lack of antenatal care follow up, lack of support to get health service, and unsatisfactory delivery services in the health facilities were found to be reason for preference of home delivery among postnatal mothers. These study finding is in line with other studies results in Ethiopia, Nigeria, Nepal, Kenya and Tanzania respectively [15,18,20,22,[27][28][29][30]32].…”
Section: Discussionsupporting
confidence: 92%
“…Out of the thirty-one women interviewed, twenty-four preferred to deliver at health facilities, six preferred home deliveries and only one preferred delivery at a prayer camp. The preference of majority of the women to deliver in a healthcare facility is consistent with studies that have been conducted in countries such as Democratic Republic of Congo [15], Kenya [16], Nepal [17], Tanzania [18] and even an earlier study across the three ecological zones of Ghana [19]. In all these studies, majority of the women in the sample either delivered or preferred to deliver at a healthcare institution.…”
Section: Preferred Places Of Deliverysupporting
confidence: 85%
“…The proximity of the women to a health facility was not statistically significant ( 2.47 χ 2 = ), (p-0.116), while similar study conducted in Tanzania was found the contrary to this, and they reported that distance to health facility was statistically significant (p-<0.0001), this is due to cultural variation, date variation also that study in Tanzania was conducted at rural area where getting of health facilities was problem and this study was conducted in urban where the distance was not big deal of them 24 .…”
Section: The Factors Influencing the Choice Of Obstetric Home Deliverymentioning
confidence: 62%